The Impact of Gamification on Brand Loyalty Mediated by Customer Engagement (An Empirical Study: Alfapets Users on the Alfagift Application in the Jabodetabek Area) - Susilo, Mario (Dinasti Publisher, 2024)
This study aims to examine the influence of gamification on brand loyalty through the mediating role of customer engagement. Gamification, the application of game elements in non-game contexts, is hypothesized to increase customer engagement, which ultimately strengthens brand loyalty. This study involved 180 respondents residing in Jabodetabek who are active users of the Alfapets gamification feature on the Alfagift mobile application. Data was collected through online questionnaires and analyzed using Structural Equation Modeling (SEM). The results show that gamification has a positive impact on customer engagement and brand loyalty. Furthermore, customer engagement was proven to be a significant mediating variable in the relationship between gamification and brand loyalty. The findings of this study provide implications for marketers and mobile application developers in designing strategies to enhance customer engagement and loyalty through the effective implementation of gamification elements.